Evaluación de las redes hidrosanitarias de las edificaciones de la Facultad de Ingeniería Civil de la Universidad Técnica de Machala - Cruz López, Wilson Marcelo (My University, 2022)
In the development of this work, the processes and criteria taken from the NHE water for the evaluation of the drinking water, sanitary water and rainwater networks of the buildings of the Faculty of Civil Engineering are evidenced. For this purpose, it is necessary to evaluate the Hydraulic-Sanitary Networks of these buildings through the cadastre of the drinking water and sanitary sewage networks, which allow knowing their current situation and determining the required pressures. The evaluation consisted of carrying out a cadastre of the hydraulic-sanitary networks, in order to determine if their operation is optimal or if they require extensions or improvement works, which allow services to be of good quality according to current regulations. The necessary mathematical process is detailed where the diameter of the pipes suitable for the systems is determined, calculation of probable flows, the pressures in the consumption nodes and the demand of the critical points, of which the methodology for its distribution in each building. Finally, the verification of the minimum requirements contemplated by the regulations for the correct functioning of the hydrosanitary system is carried out. From the results obtained, the pressure and speed in the sections are between 0.67 m,s and 2.55 m,s and the pressures exceed those recommended. The conclusions are based on the verification of compliance with the values obtained from the mathematical process with respect to the norm and the observation made in the field. Recommendations are made based on observation in the field.
En el desarrollo del presente trabajo se evidencian los procesos y criterios tomados de la NHE agua para evaluación de las redes de agua potable, aguas sanitarias y aguas pluviales de las edificaciones de la Facultad de Ingeniería Civil. Para el efecto es necesario evaluar las Redes Hidráulico-Sanitarias de estos edificios a través del catastro de las redes de agua potable y desagüe sanitario, que permitan conocer su situación actual y determinar las presiones requeridas. La evaluación consistía en realizar un catastro de las redes hidráulico-sanitarias, con el objeto de determinar si su funcionamiento es óptimo o requieren hacer ampliaciones u obras de mejoramiento, que permitan que los servicios sean de buena calidad de acuerdo a las normas vigentes. Se detalla el proceso matemático necesario donde se determina el diámetro de las tuberías adecuado para los sistemas, cálculo de caudales probables, las presiones en los nudos de consumo y la demanda de los puntos críticos , de los cuales se presenta la metodología para su distribución en cada edificio. Finalmente, se realiza la verificación de los requisitos mínimos que contempla la normativa para el correcto funcionamiento del sistema hidrosanitario. De los resultados obtenidos, la presión y la velocidad en los tramos están entre 0.67 m, s y 2.55 m, s y las presiones superan las recomendadas. Las conclusiones están fundamentadas en la verificación de cumplimiento de los valores obtenidos del proceso matemático respecto a la norma y la observación realizada en campo. Las recomendaciones se elaboran en función dela observación en campo.
Keywords: PUNTO DE CONSUMO; SISTEMA HIDROSANITARIO; CAUDAL PROBABLE; PUNTO CRITICO